The "Magnificent Seven Errors" in Forensic Autopsy Practice: The Italian Context. Issue 4 (December 2021) - Scendoni, Roberto; Fedeli, Piergiorgio; Cannovo, Nunzia; Cingolani, Mariano
According to the Italian legal system, forensic autopsies are performed by a medical doctor specialized in legal medicine, otherwise known as a medicolegal expert (MLE), who has a range of very complex responsibilities. Indeed, the quality of forensic autopsy activity is always questioned in courts of law; incorrect assessments are dangerous because they can jeopardize the validity of a criminal investigation and thus affect the outcome so that a real culprit may be acquitted or an innocent person convicted. Nonconformities also discredit the professionalism of the specialist who performs the autopsy. The work of a MLE implies a series of assignments and duties that should be given constant consideration, but when certain aspects of this activity are underestimated or overlooked, this can lead the expert to make mistakes with irreparable consequences for the judicial investigation. In this article, for the first time, we present a summary of seven known errors related to autopsy activity following death by unnatural causes, with the purpose of alerting MLEs who work under the Italian judicial system to the potential dangers of such errors. These relate to: oversights in autopsy technique, incorrect collection of photographic and video material, unauthorized attendance at the autopsy, missing/mistaken reporting at any stage of the forensic activity, failure to notify the party forensic consultant, using histological or toxicological nonaccredited laboratories for forensic activities, and lack of observance of the chain of custody.